Eksperimen Media Permainan Edukatif “Menyambung Huruf” dalam Pembelajaran Mahārah Al Kitābah Siswa Kelas X IIS MA Negeri 1 Sleman Tahun Ajaran 2017/2018 - Anisa Dewi Fatimah; Haerani Kadar (Mahira: Journal of Arabic Studies & Teaching, 2023)
This study aims to determine the steps in using the educational game media "Menyambung Huruf" in the learning of mahārah al-kitābah (writing skills) and to identify the significant differences in mahārah al-kitābah between the experimental class and the control class among the 10th grade students of IIS MA Negeri 1 Sleman for the 2017/2018 academic year. This research is a field study using a quantitative approach and experimental method. The data collection methods used were tests, interviews, observations, and documentation. To test the accuracy of the data, validity and reliability tests were conducted. For the validity test, expert judgment and construct validity were used with the Pearson correlation method, which correlates the score of each item with the total score. For the reliability test, the Cronbach Alpha method was used. The data analysis requirements included normality testing using the Kolmogorov-Smirnov formula and homogeneity testing using the test of homogeneity of variance. The data obtained in this study were analyzed using a t-test. The results of the study show that there is a significant difference in mahārah al-kitābah between the experimental and control classes. This was evidenced by the results of the pretest and posttest mahārah al-kitābah scores. The pretest t-test resulted in a Sig. (2-tailed) value of 0.895, indicating that Sig. (2-tailed) > 0.05. This means there was no difference in the students' mahārah al-kitābah at the beginning. The posttest t-test for the experimental and control groups resulted in a Sig. (2-tailed) value of 0.000, indicating that Sig. (2-tailed) < 0.05. This means there was a significant difference in mahārah al-kitābah after the intervention using the educational game media "Menyambung Huruf."